PENERAPAN MODEL PEMBELAJARAN TIPE TGT DENGAN APLIKASI QUZZIZ UNTUK MENINGKATKAN MOTIVASI BELAJAR DI SD MUHAMMADIYAH BLORA - Annamar Yani; Kristina Gita Permatasari (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2022)
This study aims to increase the learning motivation of fourth grade students of SD Muhammadiyah Blora after applying the TGT type cooperative learning model with Quiziz Application in learning Mathematics. The process of collecting data on students' learning motivation was collected using a learning motivation questionnaire and data on students' reading ability was obtained through a reading test. Based on the analysis, in cycle I the average score of students' motivation was 30.83 (high enough category) and in cycle II it increased to 39.77 (high category), so there was an increase from cycle I to cycle II by 8.94. In cycle I, the average score of students' reading ability was 65.86 (high category) and in cycle II it increased to 72.13 (high category), so there was an increase in reading ability from cycle I to cycle II by 6.27. The implication of this study is that the application of the TGT type cooperative learning model with word card media in learning Indonesian can increase learning motivation and reading ability of grade II semester II students at SD Muhammadiyah Blora.Keyword :TGT cooperative learning, motivation and reading ability